CIDADES INTELIGENTES, MAIS TECNOLOGIA, MAIS OPORTUNIDADES - Oliveira, Naiara Eduarda; Luiz Nery da Silva, Rogério (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
This research has as its theme the Smart cities and by clippingthe integration of information and communication technologies to provide greaterefficiency of services and meet the needs of society, through its associationto city systems. The research is justified by the wide range of sectorsbeneficiaries, such as government services, public safety, theurban mobility, the supply of energy, water and very opportunely theWaste Management. The research problem is to identify obstacles to which thisprocess takes place more broadly, with so many cities still following on the fringesof this possibility. It is crucial to identify the support systems thatcharacterize a city as smart, focused on planning, managing, andoperationalize the actions of the public power in the city. the cities programsustainable development (PCS) consists of an urban sustainability agenda that aggregatesthe political, economic, environmental, social, and cultural dimensions in planningmunicipal urban. The intention is to sensitize and mobilize the municipalities to get involved through effective public policies to structure their systems.